Occupational Prestige in Turkey in the Framework of Transforming Working Life - Lütfi Sunar (Journal of Economy Culture and Society)
Occupation is central to the study and understanding of modern society. Today, it is possible to deal with many social problems, such as education, economy, urbanization, stratification through professions. Especially in the post-industrial societies that witnessed a rapid change in the economic structure, evaluations about the social meaning and importance of the professions are of great importance. Sociology of occupations and professions in the world at all times is critical, although it was underestimated in Turkey. Neither theoretical and applied studies on the subject have been developed nor necessary conceptual and social analysis. This article is based on quantitative research conducted within the rural-urban representative sample across Turkey in 2019-2020. With this research, the occupational prestige scale that was built in 2015 has been renewed. In this paper, I am analyzing the determinants and factors of occupational prestige in Turkey. On the other hand, one of the main focuses of the paper is to discuss the change in prestige scores of occupations in the context of business and working life. As a result, to build a set of indicators for occupational and professional life, will be the main aim of this paper.